2007
DOI: 10.1007/s11250-007-9016-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of calcium, phosphorus and zinc supplementation on reproductive performance of crossbred dairy cows in Tanzania

Abstract: The effects of calcium (Ca), phosphorus (P) and zinc (Zn) supplementation on reproductive performance of grazing dairy cows was studied. Forty-eight cows in their first to third parity were allocated to eight groups of 6 animals each, based on stage of lactation and milk yield. Groups 1 (control), 2 (Ca), 3 (P) and 4 (Zn) received, respectively, no mineral supplement, 10 g Ca, 8 g P and 400 mg Zn. The rest of the groups received a combination of Ca/P, Ca/Zn, P/Zn or Ca/P/Zn. Animals were drenched daily. Ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
3
8
0
Order By: Relevance
“…Our results indicated improvement of ewes’ reproduction through the significant increase in numbers and sizes of ovarian follicles and size of corpora lutea in addition to reproductive performances parameters as days to 1st oestrus, number of services/conception, pregnancy rate and levels of estradiol and progesterone as well. Our results concerning the improvement of ewes’ reproduction and health are in agreement with studies in other species (Orden et al., ; Phiri et al., ). Decreased phosphorus concentration as a mineral supplement did not modify the reproductive parameters in beef cows (Costa, Ponsano, de Souza, & Malafaia, ) while others reported that phosphorus in mineral supplements was associated with good reproductive performance in ruminants (McDowell, Conrad, Ellis, & Loosli, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results indicated improvement of ewes’ reproduction through the significant increase in numbers and sizes of ovarian follicles and size of corpora lutea in addition to reproductive performances parameters as days to 1st oestrus, number of services/conception, pregnancy rate and levels of estradiol and progesterone as well. Our results concerning the improvement of ewes’ reproduction and health are in agreement with studies in other species (Orden et al., ; Phiri et al., ). Decreased phosphorus concentration as a mineral supplement did not modify the reproductive parameters in beef cows (Costa, Ponsano, de Souza, & Malafaia, ) while others reported that phosphorus in mineral supplements was associated with good reproductive performance in ruminants (McDowell, Conrad, Ellis, & Loosli, ).…”
Section: Discussionsupporting
confidence: 93%
“…Current investigation showed a beneficial effect of phosphorous supplementation on reproductive performance in anoestrous Farafra ewes at late spring and early summer which is characterized by poor reproductive performance (Kleemann & Walker, ; Marai, El‐Darawany, Fadiel, & Abdel‐Hafez, ). Signs of phosphorus deficiency are characterized by delayed onset of puberty, failure of oestrus, silent oestrus or irregular, long period of inter lambing, and still born or weakly expelled offspring or even death of embryos due to lack of uterine muscle tone (Kumar, ; Phiri et al., ). In the present study, phosphorus groups had higher ewes showing oestrus and ovulation which support previous studies (Kleemann & Walker, ; Marai et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In another aspect, food or nutrient is a critical factor in regulating mammalian reproductive performance (Predavec, 2000). Amino acids (Mateo et al, 2007), vitamins (Kolodziej & Jacyno, 2005), and minerals (Phiri, Nkya, Pereka, Mgasa, & Larsen, 2007) are well established in animal nutrition for the enhancement of reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of Se and Vitamin E have been shown to decrease the incidence of retained placenta, metritis and increased the rate of uterine involution [12]. Calcium and Phosphorus are essential to ensure proper reproductive health and productivity [13]. Phosphorus is commonly referred to as the "fertility" mineral [14].…”
Section: Introductionmentioning
confidence: 99%